Cognitive adaptations to stressful environments when childhood adversity enhances adult executive function. [article]. - Mittal, Chiraag; Griskevicius, Vladas; Simpson, Jeffry A.; Sung, Sooyeon; Young, Ethan S.
Can growing up in a stressful childhood environment enhance certain cognitive functions? Drawing participants from higher-income and lower-income backgrounds, we tested how adults who grew up in harsh or unpredictable environments fared on 2 types of executive function tasks: inhibition and shifting. People who experienced unpredictable childhoods performed worse at inhibition (overriding dominant responses), but performed better at shifting (efficiently switching between different tasks). This finding is consistent with the notion that shifting, but not inhibition, is especially useful in unpredictable environments. Importantly, differences in executive function between people who experienced unpredictable versus predictable childhoods emerged only when they were tested in uncertain contexts. This catalyst suggests that some individual differences related to early life experience are manifested under conditions of uncertainty in adulthood. Viewed as a whole, these findings indicate that adverse childhood environments do not universally impair mental functioning, but can actually enhance specific types of cognitive performance in the face of uncertainty. -- (from the authors)
Keywords: Life history theory-Periodicals.; Stressful childhood environment-Periodicals.; Uncertainty-Periodicals.